Speculative Attacks - Guidotti, Pablo (IMF Working Papers; Working Paper ;, 1991)
A brief survey of the literature on speculative attacks is provided. The nature and causes of balance-of-payments crises, the implications for the behavior of the current account and the real exchange rate are discussed. Also, potential areas for future research on balance-of-payments crises are suggested.